Effect of saphenous vein space packing in conventional varicose vein surgery - P. B., Thrishuli; K. J., Shashank; S. R., Divakar; Kamath, Akshata (International Journal Of Community Medicine And Public Health, 2019)
Background: Varicose veins are common. The prevalence has been variously reported from as little as 2% to over 20% in population studies. Management of varicose vein disease has changed drastically over the past decades. Since its introduction, surgery has gone through several stages of evolution until the method of ligation with stripping eventually became and remained the standard for a long time. The objective was to study the effect on Saphenous vein space packing in conventional varicose vein surgery on intra-operative bleeding and post-operative patient recovery. Methods: A prospective comparative study was conducted in JSS Hospital, Mysuru from August 2016 to October 2018. A total of 60 patients were selected for the purpose of the study based on the inclusion and exclusion criteria. The patient was passed on post operative day 2, 4, 7 and 30. The study population was divided into 2 groups, Group 1: 30 patients undergoing varicose vein surgery with packing and Group 2: 30 patients undergoing traditional varicose vein surgery without packing. Results: On pre-operative evaluation of GSV diameter, the mean diameter was found to be 8.20±2.3 mm in the conventional group and 7.30±1.82 mm in vein packing technique. The pain was found to be more in conventional group than Saphenous vein packing technique and score was found to statistically significant between the two groups on day 2 and 4. Conclusions: Saphenous vein space packing is an easy, economical and effective way of reducing post-operative pain in conventional varicose vein surgery.